PENINGKATAN KEMAMPUAN PENGETAHUAN BANGUN DATAR MELALUI MODEL PROBLEM BASED LEARNING (PBL) PADA SISWA KELAS IV SDN 3 SUKARAPIH KECAMATAN CIBEUREUM KABUPATEN KUNINGAN - Indra Cahya Sylviya Aullia Ikhwanni; Aiman Faiz; Nurkholis (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study was motivated by the low ability of mathematical knowledge of flat building material in fourth grade students of SD Negeri 3 Sukarapih. The purpose of this study was to determine the improvement of mathematical knowledge ability of flat building material through the PBL model; This type of research uses Classroom Action Research with planning, implementation, observation, and reflection steps. This PTK was carried out with two cycles. Cycle I was conducted on 3 May 2023 and cycle II was conducted on 10 May 2023. The research was conducted in class IV SDN 3 Sukarapih with a total of 23 students consisting of 11 boys and 12 girls; The results showed an increase in mathematics skills. The improvement was known by the test results in Cycle I and Cycle II which showed an increase in the average score and percentage of classical completeness. The average student score in the initial condition (pre-cycle) was 69 with a classical completeness of 35% (8 students) out of 23 students who achieved a score ≥ 75 (KKM score). Cycle I was 76 with a classical completeness of 65% (15 students) achieving a score ≥ 75. Cycle II was 82 with a classical completeness of 87% (20 students) achieving a score ≥ 75. There was an increase in the percentage of learning completeness by 22% from cycle I to cycle II; the conclusion is that the PBL model can improve mathematics skills.